Ch `S=( x/(x^2-36)-(x-6)/(x^2+6x)):(2x-6)/(x^2+6x)+x/(6-x)` `a)` Ruts gọn S b) Tìm x để gias trị `S=-1`

Ch `S=( x/(x^2-36)-(x-6)/(x^2+6x)):(2x-6)/(x^2+6x)+x/(6-x)`
`a)` Ruts gọn S
b) Tìm x để gias trị `S=-1`

2 bình luận về “Ch `S=( x/(x^2-36)-(x-6)/(x^2+6x)):(2x-6)/(x^2+6x)+x/(6-x)` `a)` Ruts gọn S b) Tìm x để gias trị `S=-1`”

  1. S=(x/(x^2-36)-(x-6)/(x^2+6x)) : (2x-6)/(x^2+6x)+x/(6-x)
    (ĐKXĐ: x ne ±6, x ne 0, x ne 3)
    =[x/((x-6)(x+6))-(x-6)/(x(x+6))] * (x^2+6x)/(2x-6)+x/(6-x)
    =(x^2-(x-6)^2)/(x(x-6)(x+6)) * (x(x+6))/(2(x-3))+x/(6-x)
    =((x-x+6)(x+x-6))/(x(x-6)(x+6)) * (x(x+6))/(2(x-3))+x/(6-x)
    =(6(2x-6))/(x(x-6)(x+6)) * (x(x+6))/(2(x-3))+x/(6-x)
    =(12(x-3))/(x(x-6)(x+6)) * (x(x+6))/(2(x-3))+x/(6-x)
    =6/(x-6)+x/(6-x)
    =6/(x-6)-x/(x-6)
    =(6-x)/(x-6)
    =(-(x-6))/(x-6)
    =-1

    Trả lời
  2. Giải đáp+Lời giải và giải thích chi tiết:
    a)
    S=({x}/{x^2-36}-{x-6}/{x^2+6x}):{2x-6}/{x^2+6x}+x/{6-x}
    Điều kiện : x\ne0;x\ne3;x\ne+-6
    =({x}/{(x+6)(x-6)}-{x-6}/{x(x+6)}):{2x-6}/{x(x+6)}+x/{6-x}
    =[{x.x-(x-6)(x-6)}/{x(x+6)(x-6)}] . {x(x+6)}/{2x-6}+x/{6-x}
    ={x^2-(x-6)^2}/{x(x+6)(x-6)} . {x(x+6)}/{2(x-3)}+x/{6-x}
    ={x^2-(x-6)}/{2(x-3)} -x/{x-6}
    ={12x-36}/{2(x-3)(x-6)} -{x}/{x-6}
    ={12(x-3)}/{2(x-3)(x-6)} -{x}/{x-6}
    ={6}/{x-6} -{x}/{x-6}
    =-{x-6}/{x-6}=-1
    b)
    Xem lại đề.

    Trả lời

Viết một bình luận

Câu hỏi mới